Diversity of the RFamide Peptide Family in Mollusks - Zatylny-Gaudin, Celine; Favrel, Pascal (Frontiers in Endocrinology, 2014)
Since the initial characterization of the cardioexcitatory peptide FMRFamide in the bivalve mollusk Macrocallista nimbosa, a great number of FMRFamide-like peptides (FLPs) has ibeen identified in mollusks. FLPs were initially isolated and molecularly characterized in model mollusks using biochemical methods. The development of recombinant technologies and more recently of genomics has boosted knowledge on their diversity in various mollusk classes. Today, mollusk FLPs represent approximately 75 distinct RFamide peptides that appear to result from the expression of only five genes: the FMRFamide-related peptide (FaRP) gene, the LFRFamide gene, the luqin gene, the neuropeptide F (NPF) gene and the cholecystokinin/sulfakinin (CCK/SK) gene. FLPs display a complex spatiotemporal pattern of expression in the central and peripheral nervous system. Working either as neurotransmitters, neuromodulators or neurohormones, FLPs are involved in the control of a great variety of biological and physiological processes including cardiovascular regulation, osmoregulation, reproduction, digestion and feeding behavior. From an evolutionary viewpoint the major challenge will then logically concern the elucidation of the FLP repertoire of orphan mollusk classes and the way they are functionally related. In this respect, deciphering FLP signaling pathways by characterizing the specific receptors these peptides bind remains another exciting objective.